Nutrition and Physical Therapy in the Prevention and Treatment of Endometriosis - Krzemińska, Paulina; Gołębski , Maciej; Nowak , Wojciech; Mikołajczyk , Jagoda; Kukla , Zuzanna; Mieruszyńska , Stella; Sadowska , Izabela; Kołodziej , Joanna; Sawicki , Mirosław; Włosiański , Jakub; Musialik , Sebastian (Quality in Sport, 2025)
Endometriosis is a chronic inflammatory disease which the benign growth of functioning endometrial glands and stroma in ectopic locations, i.e. outside the uterine cavity. In the 60s of the twentieth century, endometriosis had become the main cause of surgery in women. Sick women suffering from this condition often have non-specific symptoms, such as pelvic pain and are often associated with the menstrual cycle. can lead to reduced mental, physical, and social well-being and a lower quality of life. There are many factors that predispose to the onset and course of the disease. Some of them are physical activity and diet. There is a lack of high-quality, robust, randomized studies. However, available studies show that diet and physical activity reduce inflammation that occurs in endometriosis. They have a positive effect on markers of oxidative stress. The purpose of this review is to provide knowledge about the symptoms, effects of nutrition and physical activity in the prevention and treatment of endometriosis.